2017
DOI: 10.1097/icb.0000000000000336
|View full text |Cite
|
Sign up to set email alerts
|

Acute Serous Retinal Detachment in Idiopathic Pulmonary Arterial Hypertension

Abstract: Transient severe choroidal filling defects with subretinal exudation may be observed in idiopathic pulmonary arterial hypertension. The present case raised the questions of the triggering factor of the acute decompensation of the blood-retinal barrier and the cause of its spontaneous regression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Uveal effusion, choroidal detachment, exudative retinal detachment and retinal vein occlusion has been described. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 Furthermore, hypoxia induces vascular endothelial growth factor in ischemic tissues including the retina. 4 A multi-disciplinary approach is necessary to achieve cardiopulmonary hemodynamic balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uveal effusion, choroidal detachment, exudative retinal detachment and retinal vein occlusion has been described. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 Furthermore, hypoxia induces vascular endothelial growth factor in ischemic tissues including the retina. 4 A multi-disciplinary approach is necessary to achieve cardiopulmonary hemodynamic balance.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular complications are uncommon but may include secondary glaucoma, retinal vascular occlusion, choroidal effusion, and serous retinal detachment. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 We describe herein a patient with severe pulmonary hypertension who developed secondary open-angle glaucoma and serous macular detachments resembling central serous retinopathy associated with choroidal engorgement documented with enhanced depth optical coherence topography (ED-OCT).…”
Section: Introductionmentioning
confidence: 99%
“…7 Aside from CRVO, other associated ocular findings that have been hypothesized to be due to vascular congestion include uveal effusion syndrome, serous retinal and macular detachment, choroidopathy, retinal pigment epithelial tear, branch retinal vein occlusion, and angle-closure glaucoma. [8][9][10][11][12][13] It is essential to keep in mind that CRVO is a multifactorial disease. In addition to vascular congestion, the elevated IOP in both eyes may have predisposed our patient to the development of CRVO.…”
Section: Discussionmentioning
confidence: 99%
“…Based on available evidence, the ocular manifestations of PAH including, uveal effusion syndrome, exudative retinal detachment, venous stasis retinopathy, central retinal vein occlusion, choroidal detachment, delayed choroidal perfusion on fluorescein angiography, are thought to be related to the venous hypertension, causing circulatory disorders and thrombotic events, primarily in choriocapillaries 6–14 . In a recent study, Nickel and colleagues reported that PAH may be associated with an increase in retinal microvascular tortuosity 15 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Based on available evidence, the ocular manifestations of PAH including, uveal effusion syndrome, exudative retinal detachment, venous stasis retinopathy, central retinal vein occlusion, choroidal detachment, delayed choroidal perfusion on fluorescein angiography, are thought to be related to the venous hypertension, causing circulatory disorders and thrombotic events, primarily in choriocapillaries. [6][7][8][9][10][11][12][13][14] In a recent study, Nickel and colleagues reported that PAH may be associated with an increase in retinal microvascular tortuosity. 15 Although this recent evidence has shown that the vasculature of the retina and pulmonary circulation share some common characteristics, to our knowledge, no study has investigated the possible relationship and interaction between retinal microcirculation and hemodynamic measurements of pulmonary circulation in patients with PAH.…”
mentioning
confidence: 99%